Immunotherapy in metastatic renal cell carcinoma: Insights from a Dutch nationwide cohort - Hilin Yildirim; Anke Richters; Adriaan D. Bins; Arnoud W. Postema; Maureen J.B. Aarts; Martijn G.H. van Oijen; Patricia J. Zondervan; Katja K.H. Aben (European Urology Open Science)
Targeted therapy with tyrosine kinase inhibitors (TKIs) was the standard of care for metastatic renal cell carcinoma (mRCC) until recently, when new first-line combinations with immuno-oncology (IO) agents were approved. We evaluated IO uptake in both first-line and later-line treatment in routine clinical practice in the Netherlands. Patients diagnosed with synchronous mRCC between 2018 and 2022 were identified from the population-based Netherlands Cancer Registry (n = 2621). The median age was 70 yr and 58% of patients had clear-cell RCC. Overall, 55% received at least one line of systemic therapy, 7% underwent cytoreductive nephrectomy without systemic therapy, and the remaining 37% received best supportive care. In the systemic treatment cohort, first-line TKI use decreased from 94% in 2018 to 21% in 2022, while IO use increased from 6% to 79%. Data from 2019–2020 show that 32% and 10% of patients received any second-line and third-line therapy, respectively. The 3-yr overall survival rate for patients with synchronous mRCC increased from 20% (95% confidence interval [CI] 16–23%) in 2018 to 28% in 2021 (95% CI 24–33%). Our analysis shows that IO approvals for mRCC since 2019 have led to an immediate and large increase in IO use to approximately 80% of patients who receive systemic treatment. Patient summary: Since 2019, systemic treatments for metastatic kidney cancer have shifted from drugs targeting selected proteins to immunotherapy. Our results show trends over time for more favorable characteristics among patients receiving systemic treatment and improvements in survival.